Synthesis and Characterization of Short Saccaharum Cilliare Fibre Reinforced Polymer Composites - A. S. Singha; Vijay Kumar Thakur (E-Journal of Chemistry)
This paper deals with the synthesis of short Saccaharum Cilliare fibre (SC) reinforced Urea-Formaldehyde (UF) matrix based polymer composites. Present work reveals that mechanical properties such as: tensile strength, compressive strength, flexural strength and wear resistance of the UF matrix increase up to 30% fibre loading(in terms of weight) and then decreases for higher loading when fibers are incorporated into the matrix polymer. Morphological and Thermal studies of the matrix, fibre and short fibre reinforced (SF-Rnf) green composites have also been carried out. The results obtained emphasize the applications of these fibres, as potential reinforcing materials in bio based composites.